Topological analysis of para‐line graph of Remdesivir used in the prevention of corona virus. Issue 22 (30th August 2021) - Liu, Jia‐Bao; Singaraj, Rosary Maria
Abstract: Topological indices are the molecular descriptors that characterize the formation of chemical compounds and they assist us to predict certain physical–chemical properties like molar refraction, molar volume, chromatographic behavior, boiling point, heat of vaporization and partition coefficient. The computation of the topological index of a drug design enable researchers to have a high quality conception of the physical science and bioorganic characteristics of drugs. Reverse degree based topological indices play important role for calculation of topological descriptor. Para‐line graphs are used to illustrate the molecular structure in another way and these illustrations are valuable in structural chemistry. In this article, we present some reverse degree based topological indices namely, the reverse general Randic index, the reverse atom bond connectivity index, the reverse geometric arithmetic index, the reverse forgotten index, the reverse Balaban index and different types of Zagreb indices for the para‐line graph of Remdesivir. The results attained can help in the design of new medicine for the prevention of corona virus. Abstract : Topological indices are the molecular descriptors that characterize the formation of chemical compounds and they assist us to predict certain physical–chemical properties like molar refraction, molar volume, chromatographic behavior, boiling point, heat of vaporization and partition coefficient. The computation of the topological index of a drug design enable researchers to have a high quality conception of the physical science and bioorganic characteristics of drugs. Reverse degree based topological indices play important role for calculation of topological descriptor. Para‐line graphs are used to illustrate the molecular structure in another way and these illustrations are valuable in structural chemistry. In this article, we present some reverse degree based topological indices namely, the reverse general Randic index, the reverse atom bond connectivity index, the reverse geometric arithmetic index, the reverse forgotten index, the reverse Balaban index and different types of Zagreb indices for the para‐line graph of Remdesivir. The results attained can help in the design of new medicine for the prevention of corona virus. (A) Comparison of the reverse Randic index of the para‐line graph of Remdesivir for α = 1, − 1, 1 2, − 1 2 where red, blue, yellow and green denotes the reverse Randic index for α = 1, − 1, 1 2, − 1 2 respectively; (B) comparison of the reverse atom bond connectivity index ℜ ^ ABC L S G, the reverse geometric arithmetic index ℜ ^ GA L S G, the reverse Balaban index ℜ ^ J L S G and the reverse forgotten index ℜ ^ F L S G where red, cyan, brown, and navy denotes the reverse ℜ ^ ABC L S G, ℜ ^ GA L S G, ℜ ^ J L S G and ℜ ^ F L S G respectively. (C) Comparison of the reverse first Zagreb index ℜ ^ M 1 L S G, the reverse second Zagreb index ℜ ^ M 2 L S G, the reverse first Zagreb coindex ℜ ^ M ¯ 1 L S G and the reverse second Zagreb coindex ℜ ^ M ¯ 2 L S G where red, blue, green and yellow denotes the reverse ℜ ^ M 1 L S G, ℜ ^ M 2 L S G, ℜ ^ M ¯ 1 L S G and ℜ ^ M ¯ 2 L S G respectively. (D) Comparison of the reverse first redefined Zagreb index ℜ ^ Re ZG 1 L S G, the reverse second redefined Zagreb index ℜ ^ Re ZG 2 L S G and the reverse third redefined Zagreb index ℜ ^ Re ZG 3 L S G, where red, blue and green are the ℜ ^ Re ZG 1 L S G, ℜ ^ Re ZG 2 L S G and ℜ ^ Re ZG 3 L S G respectively. (E) Comparison of the reverse hyper Zagreb ℜ ^ HM L S G, the reverse first multiple Zagreb index ℜ ^ PM 1 L S G and the reverse second multiple Zagreb index ℜ ^ PM 2 L S G where red, green and blue denotes ℜ ^ HM L S G, ℜ ^ PM 1 L S G and ℜ ^ PM 2 L S G respectively.